Neurodegeneration in ocular and central nervous systems: optical coherence tomography study in normal-tension glaucoma and Alzheimer disease - ÇERMAN, EREN; ERASLAN, MUHSİN; ÇEKİÇ, OSMAN; ŞAHİN, ÖZLEM; DERİCİOĞLU, VOLKAN (TUBITAK SCIENTIFIC & TECHNICAL RESEARCH COUNCIL TURKEY, 2015)
Background/aim: To evaluate, in vivo, the optical coherence tomography (OCT) of the retinal nerve fiber layer (RNFL) and ganglion cell complex (GCC) in patients with normal-tension glaucoma (NTG) and those with Alzheimer disease (AD) in comparison with healthy subjects. Materials and methods: This cross-sectional study included 18 patients with NTG, 20 with AD, and 20 control subjects. An ophthalmologic examination and OCT scans of both eyes were performed in all patients. Results: There was a significant reduction in peripapillary RNFL thickness and macular GCC thickness and a significant increase in the global loss volume (GLV) rate in both the NTG and AD patients when compared to the control subjects (P = 0.004, P = 0.006, P < 0.001, respectively). The statistical evaluation showed no difference in any RNFL or GCC parameters between the AD and NTG groups (P > 0.05). There was a negative correlation between disease duration and average RNFL and GCC thicknesses (r = -0.350, P = 0.027 and r = -0.471, P = 0.002, respectively) and a positive correlation between duration and GLV (r = 0.427, P = 0.006) in the AD group. Conclusion: The average RNFL thickness, GCC thickness, and GLV rates may help in the diagnosis of AD as an additional examination and may provide some important clues about the duration of the disease.
Keywords: Optical coherence tomography; Alzheimer disease; normal-tension glaucoma; retinal nerve fiber layer; ganglion cell complex; OPEN-ANGLE GLAUCOMA; RETINAL VESSEL DIAMETER; GANGLION-CELL; FIBER LAYER; COGNITIVE IMPAIRMENT; THICKNESS; RISK; ABNORMALITIES; DEGENERATION; HYPOTHESIS